1971
DOI: 10.1029/jb076i002p00545
|View full text |Cite
|
Sign up to set email alerts
|

Relation of gravity to elevation and rejuvenation of blocks in India

Abstract: An analysis of free‐air, Bouguer, Pratt‐Hayford (D = 113.7 km), and Airy‐Heiskanen (T = 30 km) anomalies visa vis elevation in India indicates that on an over‐all basis isostatic equilibrium prevails in India. Regression study of Bouguer anomalies versus elevation made by grouping the data according to tectonic and geologic units shows that the Bouguer anomaly decreases rather slowly with the increase in elevation over the Himalayas, Aravallis, Nilgiris, Eastern Ghats and the Assam plateau, all of which are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…This points to a conductivity high in the Aravalli-Cambay region, where high heat flow and gravity values are also reported (Verma et al, 1968;Qureshy, 1970). The geomagnetic data of Sabhawala, Yangi-Bazar and Alma-Ata, however, do not reveal any unusual characteristics of the asthenosphere beneath the Pamir-Himalaya.…”
Section: The Trap Effectsupporting
confidence: 62%
“…This points to a conductivity high in the Aravalli-Cambay region, where high heat flow and gravity values are also reported (Verma et al, 1968;Qureshy, 1970). The geomagnetic data of Sabhawala, Yangi-Bazar and Alma-Ata, however, do not reveal any unusual characteristics of the asthenosphere beneath the Pamir-Himalaya.…”
Section: The Trap Effectsupporting
confidence: 62%
“…Most of these gravity highs are associated with synclinal structures filled with sedimentary/metasedimentary formations, interbedded with basic intrusives in the form of lavas or gabbroanorthosite masses which have taken place during different orogenic cycles (Quereshy et al, 1972;Verma et al, 1984;Pal et al, 2006). It is well supported by the gravity high observed over the IOG, Singhbhum Group, Dhanjori and Simlipal basins (Quereshy, 1971;Quereshy et al, 1972;Verma et al, 1984). Nearly all gravity lows are located over the Singhbhum granite batholiths or its margins.…”
Section: Resultsmentioning
confidence: 50%
“…It is observed that in recently activated areas that are characterized by high elevations there is thickening of low velocity layer as well as of the crust, and that at the same time some heavy material from the mantle moves and is incorporated into the crust (Quereshy, 1971). These factors tend to reduce the effective density contrast between the crust and sub-crust in elevated regions and at the same time would increase density contrasts within the crustal layers, causing Bouguer anomalies that may not be as low as required by the average elevation.…”
Section: Resultsmentioning
confidence: 98%
“…In topographic highs like Nilgiri positive free air, Bouguer and isostatic residual anomalies clearly indicate an excess of mass beneath the region. QURESHY (1971QURESHY ( , 1981 opined that the uplift of the Nilgiri hill was caused by thickening of the crust through Vol. 168, (2011) Insights into the Crustal Structure and Geodynamic Evolution incorporation of heavy material moving from the upper mantle into the crust.…”
Section: Isostatic Residual Anomalymentioning
confidence: 99%
“…SUBRAHMANYAM and VERMA (1980), however, hold that the isostatic residual anomaly does not seem to be controlled by topography as it spreads over both the low-lying Palghat Gap/coastal plains and the elevated Western Ghats. The magnitude of negative isostatic residual anomaly could be explained by a number of factors, singly or collectively, such as lighter density material like granite, an undissipated root of the Western Ghats, a local decrease in upper mantle density, probably caused by incorporation of the root into the mantle, or development of a low-density zone in the upper mantle resulting from some deep-seated phenomena that might have caused the epeirogenic uplift of the SGT (QURESHY, 1971(QURESHY, , 1981. How the condition of isostasy is maintained is not very clear, but it does seem that some sort of material exchange between the crust and upper mantle is involved (QURESHY, 1981;GUPTA and RAI, 2005).…”
Section: Isostatic Residual Anomalymentioning
confidence: 99%